2017
DOI: 10.22190/fumb161027001t
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis Hominis: a Mysterious and Commonly Disregarded Parasite

Abstract: Abstract. Blastocystis hominis (B. hominis) is an anaerobic, single-cell protozoan, commonly present in human and definitive characterization of Blastocystis spp. is possible at the molecular level only. The parasite is transferred by the fecal-oral route. A variety of hosts have been identified, and animal-to-human and vice versa transfers have been documented. The most common manifestations of the infection with the organism are diarrhea, abdominal pain, nausea, and bloating. This infection has also been ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The mean number of cysts detected in the infected subgroup treated by probiotics (Lactobacillus) (Tga) was 800 cysts with an SD of 28.39. The mean number of cysts detected in infected subgroup treated by combined metronidazole and probiotics (Lactobacillus) (Tgb) 520 cyst with SD= 18.4 As shown in Tables (1,2) and Figures (1). There was a decrease in mean parasitic count in all infected treated subgroups compared to positive infected non-treated control subgroup.…”
Section: Resultsmentioning
confidence: 93%
“…The mean number of cysts detected in the infected subgroup treated by probiotics (Lactobacillus) (Tga) was 800 cysts with an SD of 28.39. The mean number of cysts detected in infected subgroup treated by combined metronidazole and probiotics (Lactobacillus) (Tgb) 520 cyst with SD= 18.4 As shown in Tables (1,2) and Figures (1). There was a decrease in mean parasitic count in all infected treated subgroups compared to positive infected non-treated control subgroup.…”
Section: Resultsmentioning
confidence: 93%
“…Secretory IgA, and serum IgA, and IgG levels in Blastocystis-positive people with and without symptoms were looked into by ELISA, and the data revealed that patients with symptoms had significantly higher IgA, and antibodies reactive to Blastocystis (Mahmoud and Saleh 2003). Furthermore, (Tasić et al 2017) reported that symptomatic cases have elevated IgG titers and IgA response is weak or absent in asymptomatic infections.…”
Section: Serodiagnosismentioning
confidence: 99%
“…It is the most common parasite found in human stools, with prevalence rates as high as 50% in medium-to high-income countries and 100% in low-income countries (Stensvold et Blastocystis infection can manifest with various intestinal (diarrhoea, abdominal pain, atulence, nausea, and bloating) and extra-intestinal (hives, itching, and rashes) manifestations (El Safadi et al 2016; Tan et al 2008;Yakoob et al 2010). Furthermore, this infection has been associated with conditions such as appendicitis and peritonitis (Fréalle et al 2015), irritable bowel syndrome (Das et al 2016), and chronic in ammatory disease (Tasić et al 2017). Many investigations proved the presence of Blastocystis sp.…”
Section: Introductionmentioning
confidence: 99%